EVALUATING KEY COMPONENTS OF SOIL NUTRIENTS AND THEIR DYNAMICS UNDER MANGO CROPS IN PART OF SUDAN SAVANNA, NIGERIA - Abdulkadir, M.; Sanusi, A.; Asuku, M.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study evaluated key components of soil nutrients and their dynamics in mango (Mangifera indica) cultivated field of the Sudan Savanna, North-eastern Nigeria. Forty (40) representative soil samples were used to form eight (8) composite samples collected from eight (8) 20 x 20m quadrats at the depth of 0-30cm from mango cultivated field. These samples were prepared and tested using standard routine laboratory techniques for the analyses of particle size distribution, OM, TN, soil pH, EA, Ca2+, Mg2+, NA+, K+, AP, CEC, and BS. Principal Component Analysis (PCA) was employed to identify the main soil variables influencing nutrient dynamics under the crop. The results indicated that, only the first two components were retained for the explanation of the variables which accounted for 76% of the variance in mango cultivated field. The first component was named nutrient gradient, highlighting the dynamics of nutrient availability. The second component was named texture gradient, demonstrating the importance of soil texture in nutrient and moisture retention. Coefficient of variation and mean were also used to complement the result of the PCA. All the variables revealed relative homogeneity within the mango cultivated field. These insights are most importantly vital for smallholder farmers aiming to optimize crop yields while maintaining soil health. The study therefore, advocates the need for organic amendments and sustainable practices to improve soil fertility and structure.